Study of the dust effect and the nominal power estimation in a photovoltaic string: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Angulo Abanto, José Rubén (2020)
The amount of dust deposited on the surface of a panel depends on the environmental parameters. These are random (eg. humidity, wind speed and ambient temperature) which makes it difficult to model them theoretically. This paper describes the effect of dust by calculating the derating factor (η_polvo) and modeling its dependence over time. To achieve this, an experimental campaign was carried out in three tandem (a-Si / µc-Si) of 1.15 kW controlled in the city of Lima, divided into two periods of time. In the first period, from 07.15.2016 to 04.07.2017, the three strings were cleaned twice per week. The nominal power was calculated for days with clear skies conditions. It was found that between each string there are slight differences or mismatches in the nominal power, which is considered to estimate a correction factor (k) in order to readjust the output power. In the second stage from 05.07.2017 to 05.07.2018, the powder was allowed to deposit naturally, studying the effect of the dust on the energy fall through the reduction factor. Understanding this factor will be of importance for the maintenance operations of the ropes determined in that specific environment.